Clinicopathological and prognostic value of LINC01296 in cancers: a meta-analysis - Wei Feng; Cui Zhai; Wenhua Shi; Qianqian Zhang; Xin Yan; Jian Wang; Qingting Wang; Manxiang Li (Artificial Cells, Nanomedicine, and Biotechnology, 2019)
Objective The long intergenic non-coding RNA 01296 (LINC01296) has been reported to be overexpressed in multiple tumours. However, the role of LINC01296 in clinicopathologic and prognostic value in cancers remains completely unknown. The aim of the present meta-analysis was to comprehensively elucidate the correlation between LINC01296 with clinicopathological features and survival outcomes in tumours.Methods Electronic databases of PubMed, Web of Science, Chinese National Knowledge Infrastructure (CNKI), and Wanfang Database were used to search relevant studies. The role of LINC01296 in cancers was evaluated by pooled hazard ratios (HRs), odds ratios (ORs) and 95% confidence intervals (CIs).Results In total, nine studies compromising 720 participants were enrolled in this analysis. The pooled results showed increased LINC01296 expression could predict unfavourable overall survival (OS) (HR = 1.89, 95%CI = 1.47–2.43, p < .001). Additionally, elevated LINC01296 expression was correlated with clinical stage (OR = 2.95, 95%CI = 2.13–4.08, p < .001), lymph node metastasis (OR = 2.76, 95%CI = 2.00–3.81, p < .001), tumour size (OR = 2.80, 95%CI = 1.77–4.41, p < .001), and tumour differentiation (OR = 2.11, 95%CI = 1.36–3.27, p < .001) in patients with cancers.Conclusion The results of this meta-analysis indicated LINC01296 was a novel biomarker for prognosis and clinicopathological parameters in cancers.